The Combined Effect of Cu, Zn and Pb on Enzyme Activities in Soil from the Vicinity of a Wellhead Protection Area. Issue 3 (2nd April 2016) - Feng, Dan; Teng, Yanguo; Wang, Jinsheng; Wu, J
ABSTRACT: Heavy metals are known to have adverse effects on soil ecosystems, while soil enzyme activities are sensitive to soil pollution. This study investigated the combined effects of Cu, Zn and Pb on the activities of invertase (IN), urease (U) and alkaline phosphatase (ALP) in soil obtained from the vicinity of a wellhead protection area via an orthogonal array (OA) design method. The experimental results showed the following: (1) Cu showed higher inhibition on the activities of all three enzymes than Zn and Pb when three metals were all present in the soil sample. IN activity, U activity and ALP activity decreased as the levels of Cu increased, and ranged from 15.9% to 55.7%, 3.57% to 78.6%, and 3.23% to 75.3%, respectively. Their lowest values were found in samples at 35 days with 400 mg/kg Cu. (2) Zn and Pb had different influences on the activities of the three enzymes. The lowest IN activity (the highest reduction 58.0%) and U activity (76.8%) were observed when Zn was at the concentration of 100 mg/kg after 35 days, whereas the highest inhibitory function of Zn on ALP activity (75.3%) was at 300 mg/kg after 7 days. When the concentration of Pb increased from 35 to 350 mg/kg, the activities of IN (62.5%) and U (69.6%) were most inhibited at 35 days and 14 days, respectively. However, when Pb was at the concentration of 500 mg/kg after 14 days, ALP activity (72.0%) showed the lowest value. (3) With respect to the three hydrolases in this study, ALP was the most sensitive to the two-variable interactive effects of Cu, Zn and Pb, especially Cu × Pb. It is concluded that the soil ALP activity may be a sensitive tool for assessing additive toxic effect on soil biochemical parameters. To provide more information about the potential ecological risk of chemicals on soil ecosystems, much more should be done to clearly determine the mechanisms of the combined effects of heavy metals in soil.